Proceedings of the 46th Annual Southeast Regional Conference on XX 2008
DOI: 10.1145/1593105.1593133
|View full text |Cite
|
Sign up to set email alerts
|

Service learning meets mobile computing

Abstract: Computer Science educators are often frustrated in their attempts to demonstrate the power and relevance of their discipline in a classroom setting. Increasingly, educators are turning to carefully designed service learning projects to provide that experience.This paper describes a year-long service learning project in which we developed a working prototype of a mobile, locationaware tour for the Bonsai Exhibition Garden of the North Carolina Arboretum. The tour is a web-based, customizable, multimedia present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…[5,53,80]), service learning experiences (e.g. [74,78]), sustainability (e.g. [15,33]), and within fields such as HCI (e.g.…”
Section: Related Workmentioning
confidence: 99%
“…[5,53,80]), service learning experiences (e.g. [74,78]), sustainability (e.g. [15,33]), and within fields such as HCI (e.g.…”
Section: Related Workmentioning
confidence: 99%
“…Back in 1971, Ben Schneiderman argued that students should be equally stimulated to study sociological modeling as faster algorithms for eigenvalue calculations [26]. More recently, there has been a growing body of initiatives (HFOSS [20,29], ICT4D [12], ICT4Peace [13], LIMITS [15], ACM Compass [1]) and experience reports describing CSG-Ed in upper division courses, such as software engineering [4,6,19], capstone courses [2,14,27], and service learning experiences [21,22,25]. Unfortunately, the majority of examples in the literature focus on upper-division courses; well beyond the crucial decision influencing introductory course.…”
Section: Change Starts At Homementioning
confidence: 99%
“…Other educators have demonstrated that mobile application programming is accessible to beginning computer science students by integrating it into the CS1/CS2 beginning programming sequence [18,21]. There are also student mobile programming projects for non-profit organizations [24,4] that apply human computer interaction concepts to user interface design and development. Permission to make digital or hard copies of all or part of this work for personal or classroom use is granted without fee provided that copies are not made or distributed for profit or commercial advantage and that copies bear this notice and the full citation on the first page.…”
Section: Related Workmentioning
confidence: 99%